Wolves in human-dominated landscapes of Northwestern Iberian Peninsula - Llaneza Rodríguez, Luis
This thesis has focused on the study of different aspects of wolf (Canis lupus) ecology to try explain its presence and persistence in human-dominated landscapes. We analyzed factors affecting the presence of the wolf in relation to the availability of food, landscape features and human pressure.We found that the group of predictors related with landscape attributes (altitude, roughness and refuge) strongly determined wolf occurrence, followed by human pressure and food availability. To study changes in the diet of wolves in last decades in western Galicia, we have compared data from 102 stomachs collected between 1970-1985 and the data from 93 wolf stomachs collected between 2002-2014. We discuss the potential implications of the observed shift in the diet of wolves on human-wolf conflicts. We also call attention on the pressing need to integrate policies into biodiversity conservation to anticipate future conservation and management dilemmas. We studied the factors determining homesites wolf selection in relation to food availability, human pressure and refuge availability in human-dominated landscapes. We compared the characteristics of 33 homesites located in Western Galicia with 151 random points. Homesite wolf selection was not determined by food availability in the immediate vicinity. Wolves placed their homesites in areas with a high availability of unfragmented refuge, low accessibility and low human activity levels. We investigated the selection of resting sites by wolves in this human-dominated landscape by studying the spatial behaviour of 16 wolves equipped with GPS-GSM collars. Within each wolf territory, we generated several random points to contrast with observed resting sites. Wolves located their resting sites away from paved and large unpaved roads and from settlements; in addition, they significantly selected areas with high availability of horizontal (refuge) and canopy cover. We used spatial information from 29 wolves equipped with GPS-GSM collars to identify the determinants of home range ...